Analisis Dampak Penerapan PSAK 72 terhadap Kinerja Keuangan Perusahaan Sektor Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia - Intan Juliana Putri; Sari Indah Oktanti Sembiring (AKUNTANSI 45, 2026)
This study analyzes the impact of PSAK 72 (Revenue from Contracts with Customers) on the financial performance of 14 building construction companies listed on the Indonesia Stock Exchange (IDX) for the period 2015–2024. A quantitative comparative approach was employed, comparing nine financial ratios across three dimensions: liquidity (Quick Ratio, Cash Ratio, Current Ratio), profitability (GPM, NPM, ROA, ROE), and solvency (DAR, DER) between the pre-adoption (2015–2019) and post-adoption (2020–2024) periods. Samples were selected through purposive sampling and tested using the Wilcoxon Signed Rank Test. Five of nine hypotheses were accepted: Quick Ratio (H1), ROA (H6), ROE (H7), DAR (H8), and DER (H9). Cash Ratio, Current Ratio, GPM, and NPM showed no significant differences. Findings indicate that PSAK 72's impact is more pronounced on balance sheet-based variables (contract assets, contract liabilities, and equity) than on income margin variables, primarily through asset composition shifts and equity erosion resulting from changes in revenue recognition timing.